Legislation and Policies for The Employment of Foreign Worker in Korea - Yoon-Choel Choi (Sociological Jurisprudence Journal, 2018)
From the 1990s onwards, labour importation to Korea began with the introduction of industrial trainee system which later faced criticism for human and labour rights violations. From a constitutional perspective, this study aims to critically examine prominent trends of Korea laws, institutions, policies and judicial decision on foreign workers in Korea, especially unskilled workers, and to provide recommendation to remedy the problems discussed. The research method used in this research is normative law research method to conduct a literary review because of the characteristics and traditions of law. The approaches used in legal research are the statute approach, the case approach, and the conceptual approach. The result of data analysis is presented in the form of informal method by description. The results of this research are unskilled migrant labourers in Korea consist of unskilled workers and working visit migrants. Working visit is granted to those who are overseas Koreans and qualified for conditions stated in the addenda of the enforcement decree of the Immigration Act. Korea abolished the industrial trainee program and adopted â€œemployment permit systemâ€ under â€œthe act on foreign workersâ€™ employment, etc.â€ that came into force on 17 August 2004.